2005
DOI: 10.1161/01.atv.0000179599.71086.89
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 2 Plays a Role in the Bioactivation of Nitroglycerin in Humans

Abstract: Objective-Nitrates are used widely in clinical practice. However, the mechanism underlying the bioactivation of nitrates to release NO remains unclear. Recent animal data suggest that mitochondrial aldehyde dehydrogenase (ALDH2) plays a central role in nitrate bioactivation, but its role in humans is not known. We investigated the role of ALDH2 in the vascular effects of nitroglycerin (NTG) Key Words: nitroglycerin Ⅲ nitric oxide Ⅲ nitrates Ⅲ blood flow Ⅲ vasodilation N itrates have been used for Ͼ100 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 22 publications
7
79
0
Order By: Relevance
“…However, after taking sublingual nitroglycerine, the degree of brachial artery dilatation in patients with the ALDH2 *504Lys allele was significantly lower than in those with the wild-type (Xu et al 2011). These results demonstrate that the ALDH2 *504Lys allele exerts a significant effect on non-endothelium-dependent vasodilation and an insignificant effect on endothelium-dependent vasodilation, which is consistent with previous studies (Zhang et al 2004;Mackenzie et al 2005). Previous studies have confirmed that coronary spasm is significantly correlated with damaged endothelium-but not with non-endotheliumdependent vasodilation.…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (supporting
confidence: 93%
See 1 more Smart Citation
“…However, after taking sublingual nitroglycerine, the degree of brachial artery dilatation in patients with the ALDH2 *504Lys allele was significantly lower than in those with the wild-type (Xu et al 2011). These results demonstrate that the ALDH2 *504Lys allele exerts a significant effect on non-endothelium-dependent vasodilation and an insignificant effect on endothelium-dependent vasodilation, which is consistent with previous studies (Zhang et al 2004;Mackenzie et al 2005). Previous studies have confirmed that coronary spasm is significantly correlated with damaged endothelium-but not with non-endotheliumdependent vasodilation.…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (supporting
confidence: 93%
“…Recent studies have found that mitochondrial ALDH2 is also a critical enzyme for converting nitroglycerine into nitric oxide (Li et al 2006). ALDH2 inhibition can significantly reduce the vasodilatory effects of nitroglycerine (Mackenzie et al 2005;Daiber et al 2009). Another canine study also confirmed that the inhibition of ALDH2 activity can significantly reduce the dilation of canine coronary vessels (Zhang et al 2004).…”
Section: Endothelial Function and Endothelial Nitric Oxide Synthase (mentioning
confidence: 99%
“…73 In addition, despite showing a markedly reduced GTN-induced vasodilation in carriers of ALDH-2 polymorphisms and after ALDH-2 inhibition, human studies suggested that this enzyme accounts for only a half of the total bioactivation of GTN. 33 Challenging the role of ROS-induced abnormalities, Sage et al 49 reported an impaired biotransformation of GTN in venous tissue from patients treated with GTN but no cross-resistance to other NO donors and to a calcium ionophore; in this study, although the bioavailability of superoxide anion was increased in arterial segments from the same patients, short-term exposure to oxidative stress did not change GTN responsiveness. Further emphasizing the complexity of the mechanisms underlying GTN tolerance, in another study, folic acid preserved arterial, but not venous, responsiveness to sublingual GTN, 74 suggesting the existence of different mechanisms across different vascular beds.…”
Section: Unresolved Issuesmentioning
confidence: 45%
“…For instance, incubation of human vessels with an ALDH-2 inhibitor recapitulated the abnormalities associated with the development of tolerance, 32 ( Figure 5) and a loss-of-function mutation of ALDH-2 particularly frequent in Eastern Asia and Eastern Europe was found to be associated with impaired GTN metabolism and reduced responsiveness to GTN. 33 …”
Section: Aldehyde Dehydrogenase the Enzyme That Metabolizes Alcoholmentioning
confidence: 99%
“…38,39 Indeed, in an investigation into the role of ALDH-2 in the biotransformation of GTN in humans in vivo, complete ALDH-2 inhibition by disulfiram therapy only resulted in a 33% reduction in GTN responses. 40 Recently, altered phosphodiesterase 5 activity was also implicated in the development of GTN tolerance in veins. 41 In striking contrast to our findings with AS, pretreatment of vessels with DEA/NO caused marked cross-tolerance to GTN.…”
Section: Discussionmentioning
confidence: 99%